A new lizard of the Phymaturus genus (Squamata: Liolaemidae) from Sierra Grande, northeastern Patagonia, Argentina - Avila, Luciano Javier; Pérez, Cristian Hernán Fulvio; Minoli, Ignacio; Morando, Mariana (Zootaxa, 2014)
A new species of lizard of the saxicolous and viviparous genus Phymaturus from Patagonia is described. The new species is a member of the Phymaturus patagonicus species group distributed on volcanic plateaus, mountains or rocky outcrops of southern Argentina. Phymaturus yachanana sp. nov. differs from the other members of the patagonicus group by a dorsal pattern of small and medium-sized white spots on a brown background, the number of scales around the midbody, genetic differences in mitochondrial and nuclear markers, and allopatric geographic distribution in an isolated group of hills. As other species of the group, the new species is viviparous and herbivorous.